Stiffness evolution of natural hydraulic lime mortars at early ages measured through EMM-ARM - Garijo, Lucia (2019)
This paper focuses on the mechanical characterization of the early age behavior of three NHL mortars with different water/lime ratios. A vibration-based technique with continuous data recording (Elastic Modulus Measurement through Ambient Response Method - EMM-ARM) was used to measure stiffness of the different mortars that were found to range between 2.5 and 4.1 GPa on day 7. Other physical and mechanical properties such as strength and density were measured as a function of sample preparation protocols –vibrated, compacted, sealed and unsealed. After 7 days, sealed specimens led to 50% lower compressive strength and 25% lower flexural strength compared to unsealed specimens.